2020
DOI: 10.3390/life10090183
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Alpha-Synuclein Promotes a Neuroinhibitory Secretory Phenotype in Astrocytes

Abstract: Multiple system atrophy (MSA) and dementia with Lewy bodies (DLB) are α-synucleinopathies that exhibit widespread astrogliosis as a component of the neuroinflammatory response. Munc18, a protein critical to vesicle exocytosis, was previously found to strongly mark morphologically activated astrocytes in brain tissue of MSA patients. Immunofluorescence of MSA, DLB and normal brain tissue sections was combined with cell culture and co-culture experiments to investigate the relationship between extracellular α-sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In the last 10 years, only a few research papers have specifically characterized exocytosis of synaptic-like microvesicles from astrocytes (Cali et al, 2014;Stenovec et al, 2016Stenovec et al, , 2018Stenovec et al, , 2020Lasič et al, 2017;Sobieski et al, 2017;Wolfes et al, 2017;Chowdhury et al, 2018;Eersapah et al, 2019;Rituper et al, 2022), all from in vitro models. None of these works has shown any EM micrograph, and only two are showing some fluorescence immunohistochemistry with markers for vesicular markers in situ (Plá et al, 2017;Di Marco Vieira et al, 2020). Looking at in vivo studies, two recent papers characterizing neuro-glia interplay at synaptic level, suggest the involvement of SLMVs exocytosis in the process.…”
Section: State Of the Art On The Quest Of Exocytotic Organellesmentioning
confidence: 99%
“…In the last 10 years, only a few research papers have specifically characterized exocytosis of synaptic-like microvesicles from astrocytes (Cali et al, 2014;Stenovec et al, 2016Stenovec et al, , 2018Stenovec et al, , 2020Lasič et al, 2017;Sobieski et al, 2017;Wolfes et al, 2017;Chowdhury et al, 2018;Eersapah et al, 2019;Rituper et al, 2022), all from in vitro models. None of these works has shown any EM micrograph, and only two are showing some fluorescence immunohistochemistry with markers for vesicular markers in situ (Plá et al, 2017;Di Marco Vieira et al, 2020). Looking at in vivo studies, two recent papers characterizing neuro-glia interplay at synaptic level, suggest the involvement of SLMVs exocytosis in the process.…”
Section: State Of the Art On The Quest Of Exocytotic Organellesmentioning
confidence: 99%
“…The misfolded a -synuclein released by neurons is taken up by astrocytes via endocytosis and triggers a pro-inflammatory response ( Lee et al, 2010a ; Rannikko et al, 2015 ), including the secretion of pro-inflammatory and neuroinhibitory factors ( Kekesi et al, 2019 ). Astrocytic response to a -synuclein is correlated to elevated levels of the mammalian homologue of UNC-18 (Munc18) -a protein essential for vesicle exocytosis, accompanied by reactive astrocytic morphology and increased expression of IL-6 ( Di Marco Vieira et al, 2020 ). Indeed, Cavaliere and colleagues demonstrated that Lewy body fractions containing human α-synuclein are taken up more efficiently by astrocytes rather than neurons and induces high expression of endogenous α-syn while the transport of α-synuclein takes place bi-directionally between both cell types and causes astrogliosis ( Cavaliere et al, 2017 ).…”
Section: Astrocytic Modulation Of Neurodegenerationmentioning
confidence: 99%
“…Given that astrocytes produce pro-inflammatory cytokines and chemokines as a response to various stimuli, it has been proposed that such astrocytes may mediate the microglial activation detected in aSyn-related brain diseases [ 605 , 606 ]. Various WT or mutant aSyn conformations have been shown to trigger the up-regulation of pro-inflammatory modulators in astrocytes, such as ICAM-1, IL-6 and TNF-α, leading to microglial activation, neuroinflammation and neurotoxic events during PD progression [ 496 , 587 , 607 ]. Specifically, transgenic mice inducibly overexpressing the PD-related A53T mutant aSyn selectively in astrocytes exhibited reactive astrogliosis accompanied by increased inflammatory responses and microglial activation in brain regions with significant neuronal loss [ 593 ].…”
Section: Glia In the Cns: Scavengers Of Extracellular Asynmentioning
confidence: 99%